Memorandum...respecting the Belfast Congress resolution on maternity and child welfare
1930-01-28 1930 1930s 2 pages PRIVATE & CONFIDENTIAL. F.& G.P.C. 10/5/1929-30. TRADES UNION CONGRESS GENERAL COUNCIL. MEMORANDUM SUBMITTED BY THE WOMEN SANITARY INSPECTORS AND HEALTH VISITORS' ASSOCIATION RESPECTING THE BELFAST CONGRESS RESOLUTION ON MATERNITY AND CHILD WELFARE. 1. This Association strongly supports the general principle that social services rendered by Local Authorities under the Local Government, Public Health, and other Acts, should be administered by the various committees and officers of the Council according to the nature of the service to be rendered, and not according to the economic status of the recipient. 2. The policy of the Association is, therefore, in favour of all matters relating to Public Health and Maternity and Child Welfare being dealt with by the committees of the Council appointed for those services, and not by the Public Assistance Committee. 3. We are of opinion that the welfare of children under the age of five, including those placed in the care of foster-mothers, should be the concern of the Maternity and Child Welfare Committees of Councils; and that responsibilities under the Infant Life Protection Act transferred to County and County Borough Councils under the Local Government Act, should, as far as children under five years of age are concerned, devolve upon the Maternity and Child Welfare Committee in each area. 4. We suggest that the officers best fitted to carry out the duty of supervising the health and welfare of boarded-out children under the age of five are Health Visitors. It is already their duty to visit such children, and the extension 292/824/1/10